Multiplicity dependence of inclusive J/ψproduction at midrapidity in pp collisions at √s=13 TeV - Acharya, Shreyasi (2020)
Measurements of the inclusive J/ψyield as a function of charged-particle pseudorapidity density dNch/dηin pp collisions at √s=13 TeV with ALICE at the LHC are reported. The J/ψmeson yield is measured at midrapidity (|y| <0.9) in the dielectron channel, for events selected based on the charged-particle multiplicity at midrapidity (|η| <1) and at forward rapidity (−3.7 <η<−1.7and 2.8 <η<5.1); both observables are normalized to their corresponding averages in minimum bias events. The increase of the normalized J/ψyield with normalized dNch/dηis significantly stronger than linear and dependent on the transverse momentum. The data are compared to theoretical predictions, which describe the observed trends well, albeit not always quantitatively.